Cultural heritage and modern information and communication technologies - Filip, Florin Gheorghe; Ciurea, Cristian; Dragomirescu, Horaţiu; Ivan, Ion (Technological and Economic Development of Economy, 2015)
The paper presents an up-to-date view of entities of the cultural heritage sector and their relationships with other domains of human activity as well as the corresponding business models facilitated by modern information and communication technologies. The economic impact of the interactions established between various actors of the cultural economy landscape, such as cultural heritage institutions, digital “facilitators” and public, is described by using a cybernetic representation and a corresponding mathematical model. A particular emphasis is put on mobile technology-based approach to the cultural heritage sector and an example of a practical online virtual exhibition is provided.